Impact of School Chair on Left-Handed Students - Nurul Retno Nurwulan (Faculty of Engineering and Technology, Sampoerna University, 2023)
Left-handed students find it challenging to do learning activities at school since the chair are made for those who are right-handed. They must change their posture, bending their neck and lower back, in order to reach the table that is located on the right side of the chair. Consequently, left-handed students may develop musculoskeletal disorders (MSDs) as a result of prolonged awkward posture in the classroom. This study sought to assess the effect of school chairs on the risk of MSDs in left-handed students. The possibility of reducing the discomfort by providing left-handed students with the appropriate chair was also examined. The Nordic Musculoskeletal Questionnaires (NMQ) was administered to a total of 14 left-handed students to identify their discomfort related to the chair they use in the classroom. The potential benefit of the proper chair was evaluated by measuring the deviation of the neck and low back from the upright sitting position. The finding of this study showed that a proper chair for left-handed students helps students sit straight without the need for bending their neck and low back. Modifying the chair to reduce the risk of MSDs is crucial, regardless of students’ handedness.